P8 Changes in cortical activity relates to changes in balance following 4-weeks of balance training in chronic ankle instability patients. (17th September 2017) - Burcal, CB; Jeon, HJ; Gonzales, JM; Bruce, CM; Thomas, AC; Hubbard-Turner, TJ; Wikstrom, EA
Abstract : Study Design: Time-series. Objectives: To examine relationships of electroencephalographic(EEG) measures of sensorimotor control and balance outcomes in response to 4 weeks of balance training in chronic ankle instability(CAI) patients. Background: Balance training is a common therapeutic intervention for CAI patients, often resulting in improvements in clinician-oriented balance measures. The mechanisms of these improvements are currently unknown in CAI patients, however, cortical activity has not yet been measured in CAI patients during motor tasks. EEG can be used to capture coordination of cortical activity during motor tasks, and how it changes as a result of balance training. Methods and Measures: 8 CAI patients completed a 4 week balance training protocol(BTP). Balance, measured by the Star Excursion Balance Test(SEBT) and EEG were collected at baseline and after completing the BTP. Cortical activity was measuring using EEG during a dual-to-single limb transition(DSLT) and was quantified using event-related spectral perturbations(ERSP), calculating the change in the power of a signal with respect to the DSLT. ERSP was calculated in the Alpha(8–12 Hz) and Beta(14–25 Hz) bandwidths in the 250 ms prior to and 250 ms following the DSLT(AlphaPre, AlphaPost, BetaPre, BetaPost). Increases in ERSP are indicative of more coordinated activity, whereas decreases indicate more widespread activation of the cerebral cortex. Change scores (posttest-baseline) in EEG and SEBT measures were analysed using Pearson product moment correlations at an alpha of 0.10. Results: A moderate positive relationship was identified between the change in Alpha ERSP and SEBT in the posteromedial direction(p=0.045). Moderate positive correlations were identified between the change in Beta ERSP and SEBT in the anterior(p=0.071), posteromedial(p=0.049), and posterolateral(p=0.076) directions. Conclusion: The positive relationships identified suggest that patients with greater improvements in dynamic balance have an increased coordination of cortical activity following balance training. Further research is needed to clarify the direction of these results and their functional and clinical significance.